2021
DOI: 10.1186/s42397-021-00089-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of micronaire using a natural population of representative upland cotton (Gossypium hirsutum L.)

Abstract: Background Micronaire is a comprehensive index reflecting the fineness and maturity of cotton fiber. Micronaire is one of the important internal quality indicators of the cotton fiber and is closely related to the value of the cotton fiber. Understanding the genetic basis of micronaire is required for the genetic improvement of the trait. However, the genetic architecture of micronaire at the genomic level is unclear. The present genome-wide association study (GWAS) aimed to identify the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The cDNA was synthesized by using a reverse transcription kit HiScript III Q RT SuperMix for qPCR (Vazyme Biotech Co., Ltd.). Furthermore, the ChamQ Universal SYBR qPCR Master Mix Kit (Vazyme) was used to carry out qRT‐PCR verification as previously described (Song et al, 2020). The real‐time PCR primers are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA was synthesized by using a reverse transcription kit HiScript III Q RT SuperMix for qPCR (Vazyme Biotech Co., Ltd.). Furthermore, the ChamQ Universal SYBR qPCR Master Mix Kit (Vazyme) was used to carry out qRT‐PCR verification as previously described (Song et al, 2020). The real‐time PCR primers are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of a gene that encodes a fiber-preferential actin-binding protein, GhPFN2, resulted in early termination of fiber elongation and a shorter fiber phenotype . Suppression of a tubulin-interacting gene, GhMAP20L5, significantly reduced the cotton fiber cell elongation rate, fiber length, and lint percentage (Song et al, 2023).…”
Section: Crop Sciencementioning
confidence: 98%
“…Recently, live-cell imaging revealed that cotton fibers elongate by tip-biased diffuse growth (Yu et al, 2019). Multiple studies have shown that genes encoding proteins that affect the cytoskeleton are essential for cotton fiber elongation (Li et al, 2007(Li et al, , 2005Preuss et al, 2004;Song et al, 2023;Thyssen et al, 2017;Wang et al, 2009;Zhang, Han, et al, 2017). A member of the XI-K myosin protein (GhXIK) family was identified by GWAS as a major QTL for fiber length, elongation, strength, and uniformity .…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, two SNP arrays are available in cotton, a 63K SNP array and an 80K SNP array (Cai et al., 2017; Hulse‐Kemp et al., 2015b). These SNP arrays have been used to assess genetic diversity (Billings et al., 2021), perform genome‐wide association studies (GWAS) (Cai et al., 2017; Gowda et al., 2022; Song et al., 2021; Sun et al., 2017), construct genetic maps (Hulse‐Kemp et al., 2015b; Zhang et al., 2019; Zhu et al., 2021), and detect QTL for fiber quality traits, yield traits, and morphological traits (Li et al., 2016; Zhang et al., 2019; Zhu et al., 2021). However, only a few studies have reported their use in identifying novel and stable QTL and develop functional markers for fiber quality traits, yield traits, and plant height in intraspecific Upland cotton populations.…”
Section: Introductionmentioning
confidence: 99%